Identification of mitochondria-related genes in calcific aortic valve disease by integrated analysis of single-cell and bulk transcriptomic atlases - Ziling Mai; Huijun Du; Yuhan Chen; Yaner Lu; Bingchen Liu; Deqiang Sun (Journal of Physiology and Biochemistry, 2026)

Hierarchical nanofluidic membrane with improved anti-fouling performance toward osmotic energy harvesting - Yang Chen; Kexin Sun; Jie Liu; Yankang Du; Ziling Wang; Xiao Zhang; Yulei Li; Yanglei Xu; Feng Xu (Chemical Engineering Journal, 2026)

Flow-electrode capacitive deionization technology: Recent progress in electrode materials - Ziling Wang; Yiyan Dong; Xihao Kou; Yuteng Zhang; Haihui Yu; Meng Sun; Xiaohong Li; Haifeng Zhang; Li Chen (Desalination, 2026)

Cysteine-engineered MXene interlayers enable highly efficient electro- and photothermal de-icing - Haobo Mao; Qingyu Chen; Xiaoyan Ruan; Ziling Pang; Xiangying Meng; Yiqi Liu; Hanyi Huang; Kejia Chen; Jiayin Liu; Yu Yu; Songmei Wu; Lixin Yang (Chemical Engineering Journal, 2026)

Structural characterization and in vivo and in vitro anti-osteoporosis potential of two Psoralea corylifolia L. polysaccharides - Jing Yang; Ziling Tang; Chanjuan Chen; Pei Lin; Ye He; Xinsheng Yao; Beibei Zhang; Zhihong Yao; Zuocheng Qiu; Zifei Qin (Carbohydrate Polymers, 2026)

Facile Fabrication of N-Doped Graphitic Carbon-Modified g-C3N4 with Enhanced Photocatalysis Performance Under Visible Light Irradiation - Ziling Peng; Xiu Wang; Fatang Tan; Xian Zhou; Zeyu Fan; Qi Lu; Xia Chen; Yu Shi; Yu Xia (Water, Air, & Soil Pollution, 2026)

Transcriptional and functional dissection of cytochrome P450 and ABC transporters underlying tobacco tolerance in Lasioderma serricorne - Junaid Zafar; Shuhao Zhang; Rana Fartab Shoukat; Ling Huang; Ang Li; Zhanpeng Zhu; Ziling Wan; Yanqing Li; Xuewei Zhang; Chen Peng; Shuai Zhong; Xiaoxia Xu; et al. (Journal of Insect Physiology, 2026)

A small heat shock protein from Arabidopsis thaliana regulates glyceraldehyde-3-phosphate dehydrogenase in the drought tolerance - Jieru Chen; Hongting Liu; Zichun Ma; Xinyi Yu; Huiyue Ji; Sipei Huang; Xinyue Zhu; Ziling Liu; Yangyang Chen; Hai Liao; Jiayu Zhou (Plant Cell Reports, 2026)

The Application of Machine Learning in the Development of Co-Amorphous Dry Powder Inhalation - Ziling Zhou; Xian Chen; Yuxin Liu; Rongjiao Zheng; Junxiang Huang; Xin Pan; Chuanbin Wu; Junhuang Jiang (AAPS PharmSciTech, 2026)

Metabolic engineering of Halomonas cupida for co-mineralization of phenol and p-nitrophenol in high-saline wastewater - Ziling Yuan; Yujie Liu; Haomin Chen; Jing Dang; Xinyu Zhang; Xinyao Li; Ruihua Liu; Chao Yang (Journal of Environmental Management, 2026)

Metagenomic insights into diet-mediated gut microbial plasticity and functional adaptations in the tobacco beetle Lasioderma serricorne (Coleoptera: Ptinidae) - Junaid Zafar; Shuhao Zhang; Zhanpeng Zhu; Ziling Wan; Yanqing Li; Ang Li; Ling Huang; Xuewei Zhang; Chen Peng; Shuai Zhong; Fengliang Jin; Xiaoxia Xu (Journal of Stored Products Research, 2026)

Conversion of wheat straw by black soldier fly larvae and fertilization effects of frass - Xifeng Wang; Ruohan Wang; Junzhao Wei; Rui Hu; Ziling Wang; Haifeng Li; Pengxiao Chen; Jianhang Qu; Mingjun Li (Journal of Asia-Pacific Entomology, 2026)

Metabolic engineering of Pseudomonas putida for mineralization of 1,2-dichloroethane and 2,4-dichlorophenoxyacetic acid and its application in wastewater bioremediation - Xinyu Zhang; Yujie Liu; Ziling Yuan; Haomin Chen; Danyang Ma; Bingzhi Li; Ruihua Liu; Chao Yang (Journal of Environmental Chemical Engineering, 2026)

Biocontrol potential of phyllosphere fungi from diseased leaves against Colletotrichum gloeosporioides and Pseudocryphonectria elaeocarpicola - Wei Wang; Shiqi Chen; Xiaotong Luo; Yitong Li; Xingxuan Zhan; Sirun Qiu; Fengqi Wu; Bing Du; Ziling Mao; Tijiang Shan (Archives of Microbiology, 2026)

Pyrolysis of sewage sludge in molten salt environment: Effects on heavy metals distribution and environmental risks in biochar - Zeyu Fan; Qi Lu; Xian Zhou; Wei Han; Yuanyi Wang; Zhuo Fan Gao; Ziling Peng; Xia Chen (Journal of Cleaner Production, 2026)

Regional disparities in marine carbon sink development in china: From an opportunity inequality perspective - Kewei Chen; Yixiong He; Ziling Chen (Regional Studies in Marine Science, 2025)

Encapsulation of Lactiplantibacillus plantarum subsp. plantarum in oil-phase gels O/W high internal phase emulsions: Improvement of storage stability and gastrointestinal viability - Enjing Huang; Ziling Li; Fangyuan Zhou; Qinyu Chen; Jiayong He; Xiangyuan Xiong; Youfa Xie; Hongxia Gao; Liqiang Zou (Food Chemistry, 2025)

Low-temperature heat recovery: An economic approach to renovate air-impaired LiNbOCl4 electrolyte for boosted stability in high-performance all-solid-state batteries - Lin Li; Shiyu Liu; Siwu Li; Ziling Jiang; Qiyue Luo; Ziyu Lu; Miao Deng; Wenqian Tian; Jie Yang; Chen Liu; Qiao Wang; Chuang Yu (Chemical Engineering Journal, 2025)

Controllable growth of halide electrolyte crystal planes enables superior cycling stability of high-voltage all-solid-state batteries - Qiyue Luo; Siwu Li; Lin Li; Ziling Jiang; Ziyu Lu; Wenwen Hu; Miao Deng; Jie Yang; Zhenyu Wang; Chen Liu; Chuang Yu (Chemical Engineering Journal, 2025)

Ion/electron/stress-triple-regulated Li deposition via multifunctional bismuth species in sulfide-based all-solid-state lithium metal batteries - Ziling Jiang; Siwu Li; Wenwen Hu; Shiyu Liu; Lin Li; Jie Yang; Miao Deng; Ziyu Lu; Xinxin Wang; Qin Chen; Hui Yang; Chen Liu; et al. (Chemical Engineering Journal, 2025)

PhenoBee: Drone-based robot for advanced field in vivo contact-based phenotyping in agriculture - Ziling Chen; Xuan Li; Tianzhang Zhao; Xing Wei; Zhihang Song; Jialei Wang; Jin Jian (Computers and Electronics in Agriculture, 2025)

A R2R3-MYB transcription factor LmMYB111 positively regulates chlorogenic acid and luteoloside biosynthesis in Lonicera macranthoides - Yanni Liu; Juan Lou; Guohua Liu; Qingqing Li; Zhengyan Cao; Peiyin Wu; Haoyang Mashu; Zhilin Liu; Jia Deng; Ziling Yang; Jiang Guo; Ning Tang; et al. (Plant Science, 2025)

The comparative analysis between sporadic and genetic Creutzfeldt-Jakob disease in China - Xudong Li; Qidong Chen; Xinying Zou; Miaoxin Shen; Ziling Han (Acta Neurologica Belgica, 2025)

A high-precision spatial and spectral imaging solution for accurate corn nitrogen content level prediction at early vegetative growth stages - Jinnuo Zhang; Xing Wei; Zhihang Song; Ziling Chen; Jian Jin (Computers and Electronics in Agriculture, 2025)

The spatial form of traditional villages in Fuzhou area of Jiangxi Province determined via GIS methods - Yapeng Duan; Liangqing Yan; Ziling Lai; Qianting Chen; Youying Sun; Li Zhang (Frontiers of Earth Science, 2025)

A self-sustainable DNA amplification circuit for sensitive microRNA imaging - Chuanyi Liu; Ziling Huang; Zhigang Li; Xiaojiao Dai; Qingmin Chen; Min Chen; Yi Xu; Xiaomei Chen; Fuan Wang; Quansheng Chen; Jie Wei (Analytica Chimica Acta, 2025)

CpAGL18 is involved in the cross-talk of ethylene and auxin signaling in the regulation of fruit ripening in papaya - Jiahui Cai; Ziling Wu; Wang Zheng; Qiunan Zhu; Zunyang Song; Weixin Chen; Xueping Li; Xiaoyang Zhu (Postharvest Biology and Technology, 2025)

Spatial-spectral feature mining in hyperspectral corn leaf venation structure and its application in nitrogen content estimation - Zhihang Song; Xing Wei; Jinnuo Zhang; Ziling Chen; Jian Jin (Computers and Electronics in Agriculture, 2024)

Multiple DNA cycle amplification for highly efficient detection of mercury pollution in food - Ziling Huang; Chuanyi Liu; Zhigang Li; Qingmin Chen; Dong Li; Xiaomei Chen; Quansheng Chen; Jie Wei (Food Chemistry, 2024)

Based on an environmental-friendly society, material modification technique to improve the performance of the lithium-ion battery - Xuanyu Yang; Ziling Xie; Xibin Lu; Xinxin Tan; Ying Li; Chen Li (Environment, Development and Sustainability, 2024)

CpAGL18 is involved in the cross-talk of ethylene and auxin signaling in the regulation of fruit ripening in papaya - Jiahui Cai; Ziling Wu; Wang Zheng; Qiunan Zhu; Zunyang Song; Weixin Chen; Xueping Li; Xiaoyang Zhu (Postharvest Biology and Technology, 2024)

Tin-based dual-modification enabling enhanced air stability and electrochemical performance for Li5.5PS4.5Cl1.5 in all-solid-state lithium metal batteries - Jie Yang; Ziling Jiang; Chen Liu; Lin Li; Siwu Li; Zhongkai Wu; Chaochao Wei; Qiyue Luo; Long Zhang; Shijie Cheng; Chuang Yu (Chemical Engineering Journal, 2024)

Current insights into the biocontrol and biotechnological approaches for postharvest disease management of Botrytis cinerea - Faiz Ur Rahman; Qiunan Zhu; Ziling Wu; Xueping Li; Weixin Chen; Tiantian Xiong; Xiaoyang Zhu (Postharvest Biology and Technology, 2024)

Competitive encapsulation of multiple heavy metals by magnesium potassium phosphate cement: Hydration characteristics and leaching toxicity properties - Xia Chen; Xian Zhou; Zeyu Fan; Ziling Peng; Qi Lu (Waste Management, 2024)

Synthesis of sewage sludge biochar in molten salt environment for advanced wastewater treatment: Performance enhancement, carbon footprint and environmental impact reduction - Zeyu Fan; Xian Zhou; Qi Lu; Zhuo Fan Gao; Shanshan Deng; Ziling Peng; Wei Han; Xia Chen (Water Research, 2024)

Corrigendum to ‘The combination of S-doped ZIF-8 with graphene oxide for enhanced near-infrared light photocatalytic and photothermal sterilization’ [Chem. Eng. J. 455 (2023) 140857] - Ziling Zhou; Huiping Zhu; Xiangmei Liu; Yuelin Lv; Yufeng Zheng; Dafu Chen; Shengli Zhu; Zhaoyang Li; Zhenduo Cui; Shuilin Wu (Chemical Engineering Journal, 2024)

Corrigendum to “The combination of S-doped ZIF-8 with graphene oxide for enhanced near-infrared light photocatalytic and photothermal sterilization” [Chem. Eng. J. 455 (2023) 140857] - Ziling Zhou; Huiping Zhu; Xiangmei Liu; Yuelin Lv; Yufeng Zheng; Dafu Chen; Shengli Zhu; Zhaoyang Li; Zhenduo Cui; Shuilin Wu (Chemical Engineering Journal, 2024)

High-Zn wheat alleviates P-Zn antagonism by improving Zn activation, acquisition, and translocation at key growth stages - Jun Yang; Junfeng Xu; Ziling Wang; Xuemei Zhang; Zikang Guo; Li Wang; Chenrui Liu; Qing Sun; Chao Li; Yinglong Chen; Mei Shi; Zhaohui Wang (Field Crops Research, 2023)

Fully automated proximal hyperspectral imaging system for high-resolution and high-quality in vivo soybean phenotyping - Ziling Chen; Jialei Wang; Jian Jin (Precision Agriculture, 2023)

Systematic and dynamic impacts of the COVID-19 pandemic on marine economic development, air pollution and energy consumption: A case study of China's coastal regions - Chenggang Li; Yuanrui Zhang; Ziling Chen; Xue Wang; Mu Yue; Jiaqi Liu; Yuchun Jiang; Zhen Zhao; Guoli Cai (Ocean & Coastal Management, 2023)

The impact of COVID-19 on economy, air pollution and income: evidence from China - Chenggang Li; Ziling Chen; Xiaodong Wang; Yikang Wan; Zhen Zhao (Stochastic Environmental Research and Risk Assessment, 2023)

Construction of a self-sufficient DNA circuit for amplified detection of kanamycin - Yumeng Li; Qingyang Si; Chuanyi Liu; Ziling Huang; Qingmin Chen; Tianhui Jiao; Xiaomei Chen; Quansheng Chen; Jie Wei (Food Chemistry, 2023)

Ag-modification argyrodite electrolytes enable high-performance for all-solid-state lithium metal batteries - Zhongkai Wu; Chuang Yu; Chaochao Wei; Ziling Jiang; Cong Liao; Shuai Chen; Shaoqing Chen; Linfeng Peng; Shijie Cheng; Jia Xie (Chemical Engineering Journal, 2023)

Hydrodynamics of waste collection in a recirculating aquaculture tank with different numbers of inlet pipes - Jun Zhang; Zhihao Zhang; Xuan Che; Congcong Chen; Yang Gao; Ning Zhang; Dinala Maidaibieke; Xingyu Zhu; Chen Ziling (Aquacultural Engineering, 2023)

Development of human health criteria in China for benzo[a]pyrene: A comparison of deterministic and probabilistic approaches - Ziling Yu; Mingdeng Xiang; Ruixue Ma; Chuan Yi; Guocheng Hu; Xichao Chen; Yupei Liu; Yunjiang Yu (Chemosphere, 2023)

Construction of a simple dual-mode ATP-sensing system for reliable fish freshness evaluation - Qingyang Si; Yumeng Li; Ziling Huang; Chuanyi Liu; Xiaomei Chen; Jie Wei; Fuan Wang (Analytica Chimica Acta, 2023)

Co-pyrolysis technology for enhancing the functionality of sewage sludge biochar and immobilizing heavy metals - Zeyu Fan; Xian Zhou; Ziling Peng; Sha Wan; Zhuo Fan Gao; Shanshan Deng; Luling Tong; Wei Han; Xia Chen (Chemosphere, 2023)

The combination of S-doped ZIF-8 with graphene oxide for enhanced near-infrared light photocatalytic and photothermal sterilization - Ziling Zhou; Huiping Zhu; Shuilin Wu; Yuelin Lv; Yufeng Zheng; Dafu Chen; Shengli Zhu; Zhaoyang Li; Zhenduo Cui; Xiangmei Liu (Chemical Engineering Journal, 2023)

Effect of Different Colored LED Lighting on the Growth and Pigment Content of Isochrysis zhanjiangensis under Laboratory Conditions - Bu Lv; Ziling Liu; Yu Chen; Shuaiqin Lan; Jing Mao; Zhifeng Gu; Aimin Wang; Feng Yu; Xing Zheng; Hebert Ely Vasquez (Journal of Marine Science and Engineering, 2022)
Light is one of the most important environmental factors affecting the growth and reproduction of algae. In this study, the effect of various LED colors on the productivity, chlorophyll (Chl-a, Chl-b, and total Chl), protein, and carbohydrate content of Isochrysis zhanjiangensis in indoor culture was investigated. Microalgae monocultures were cultivated under five different colors (red, green, blue, yellow, and white) for twenty-one days. The microalgae cultured under red light exhibited a higher specific growth rate (0.4431 ± 0.0055 µ day−1), and under white light a higher productivity (0.0728 ± 0.0013 g L−1 day−1). The poorest performance was observed under yellow and green lights. Interestingly, green light exhibited the highest levels of chlorophylls (Chl-a, 1.473 ± 0.037 mg L−1; Chl-b, 1.504 ± 0.001 mg L−1; total Chl, 2.827 ± 0.083 mg L−1). The highest protein content was observed under the white light (524.1935 ± 6.5846 mg L−1), whereas the carbohydrate content was remarkably high under the blue light (24.4697 ± 0.0206 mg L−1). This study is important in terms of the selection of light at the appropriate color (wavelength) to increase the content of organic compounds desired to be obtained indoors with the potential for commercially produced cultures.

Genome-based analysis of SFTSV causing severe encephalitis with brain lesions - Chunjuan Wang; Li Gong; Ziling Zeng; Jie Zhang; Hongzhi Guan; Lu Chen; Weijun Chen; Yifeng Du; Shougang Guo (Journal of NeuroVirology, 2020)

The Core Role of Bacillus subtilis and Aspergillus fumigatus in Pile-Fermentation Processing of Qingzhuan Brick Tea - Qian Xu; Min Sun; Jingming Ning; Shimao Fang; Ziling Ye; Junhai Chen; Ruiyan Fu (Indian Journal of Microbiology, 2019)

Polycyclic aromatic hydrocarbons (PAHs) in multi-phases from the drinking water source area of the Pearl River Delta (PRD) in South China: Distribution, source apportionment, and risk assessment - Yunjiang Yu; Ziling Yu; Zhengdong Wang; Bigui Lin; Liangzhong Li; Xichao Chen; Xiaohui Zhu; Mingdeng Xiang; Ruixue Ma (Environmental Science and Pollution Research, 2018)

Optogenetics in neuroscience: what we gain from studies in mammals - Quanhui Chen; Ziling Zeng; Zhian Hu (Neuroscience Bulletin, 2012)